Modelling reactive transport in unsaturated concrete under evaporation and condensation processes - Chaparro, M. Carme; Saaltink, Maarten W. (Frontiers in Built Environment, 2025)
El Cabril is the low- and intermediate-level radioactive waste disposal facility in Spain. Water is collected from the drains situated in the concrete cells storing radioactive waste, indicating flow of water into these concrete cells. 2D numerical models, together with temperature and humidity measurements, suggested that this flow of water was caused by a combination of thermo-hydraulic processes occurring in the unsaturated concrete, such as capillary rise from the groundwater, evaporation, and condensation due to temperature gradients caused by seasonal temperature fluctuations outside. The objective of this work is to study the effect of these processes on the mineralogy of the concrete. Therefore, 1D reactive transport models have been developed following the 2D thermo-hydraulic conceptual model. When minerals are controlled by fast kinetics, the model results show that the cement phases precipitate and dissolve, clearly following the yearly fluctuations of condensation and evaporation. However, when minerals are controlled by slow kinetics, the reactions are less affected by the hydraulic processes. The models suggest that precipitation-dissolution could be particularly important near the air gap in the concrete, where water condenses and evaporates more easily.